Monetary Inflation and its Connection with Rising Prices - ZAITSEV, Oleksandr V. (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The relevance of this issue is due to the lack of a reasonable mechanism for inflation quantifying. Therefore, the purpose of this article is to describe the scheme for the numerical evaluation of the inflation rate, based on the money estimation by labor costs. Data for analysis were taken from the Statistical yearbooks for 1997-2015. It was established that monetary inflation shows the increase in price load per unit of labor almost by 20 times. In addition, the calculations showed that the growth rate of monetary inflation is above the growth rate of prices. The authors have substantiated a direct proportion between monetary inflation and price index, and described future prospects of research in this field.